2021
DOI: 10.1037/pspp0000208
|View full text |Cite
|
Sign up to set email alerts
|

Using 26,000 diary entries to show ovulatory changes in sexual desire and behavior.

Abstract: Previous research reported ovulatory changes in women's appearance, mate preferences, extra- and in-pair sexual desire, and behavior, but has been criticized for small sample sizes, inappropriate designs, and undisclosed flexibility in analyses. In the present study, we sought to address these criticisms by preregistering our hypotheses and analysis plan and by collecting a large diary sample. We gathered more than 26,000 usable online self-reports in a diary format from 1,043 women, of which 421 were naturall… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
140
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(162 citation statements)
references
References 99 publications
17
140
4
1
Order By: Relevance
“…Research questions that are asked at the within-person level may be concerned with (a) the development of person characteristics, (b) the explanation of variance in state measures (e.g., Rauthmann, Jones, & Sherman, 2016;Sherman et al, 2015), or (c) the explanation of sequences of events and experiences (e.g., Arslan, Schilling, Gerlach, & Penke, 2018). ESM is mostly not used to address the first question.…”
Section: Research Questions At the Within-person Levelmentioning
confidence: 99%
“…Research questions that are asked at the within-person level may be concerned with (a) the development of person characteristics, (b) the explanation of variance in state measures (e.g., Rauthmann, Jones, & Sherman, 2016;Sherman et al, 2015), or (c) the explanation of sequences of events and experiences (e.g., Arslan, Schilling, Gerlach, & Penke, 2018). ESM is mostly not used to address the first question.…”
Section: Research Questions At the Within-person Levelmentioning
confidence: 99%
“…1974; Dixson, 2012;Heistermann et al, 2001;Strassmann, 1981;Symons, 1979). However, recent studies suggest that humans might exhibit subtle cues to ovulation (Gangestad & Thornhill, 2008;Haselton & Gildersleeve, 2011), though the evidence for overt cues to ovulation remains rather weak (Arslan, Schilling, Gerlach, & Penke, 2018;Welling & Puts, 2014). Some scholars have speculated that such subtlety in signalling might have evolved to deter unwanted male attention during peak fertility or to confuse paternity certainty after conception (Deschner et al, 2004;Nunn, 1999;Wallen & Zehr, 2004;Wolfe, 1979).…”
mentioning
confidence: 99%
“…The Daily Habits and Sexuality Study (Arslan, Jünger, Gerlach, Ostner, & Penke, 2016) collected data from 1,345 women over a period of 70 days. The women were first screened on a variety of demographic criteria.…”
Section: A Longitudinal Study With a Social Network Component And Othmentioning
confidence: 99%
“…Although the participants were not formally surveyed on this, online interactions indicated that the feedback was generally well received. The complete study is reproducible from documentation on the Open Science Framework and can be imported and changed (Arslan et al, 2016). An earlier, similar study implemented in an older version of formr was recently published and is described in more detail in Arslan, Schilling, Gerlach, and Penke (2018).…”
Section: A Longitudinal Study With a Social Network Component And Othmentioning
confidence: 99%